2021
DOI: 10.3390/cancers13071678
|View full text |Cite
|
Sign up to set email alerts
|

CK2 Activity Mediates the Aggressive Molecular Signature of Glioblastoma Multiforme by Inducing Nerve/Glial Antigen (NG)2 Expression

Abstract: Nerve/glial antigen (NG)2 expression crucially determines the aggressiveness of glioblastoma multiforme (GBM). Recent evidence suggests that protein kinase CK2 regulates NG2 expression. Therefore, we investigated in the present study whether CK2 inhibition suppresses proliferation and migration of NG2-positive GBM cells. For this purpose, CK2 activity was suppressed in the NG2-positive cell lines A1207 and U87 by the pharmacological inhibitor CX-4945 and CRISPR/Cas9-mediated knockout of CK2α. As shown by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…With the advent of the CRISPR/Cas9 tool, it has been possible to produce viable knockout cancer cells for each CK2 catalytic subunit. Even if the production of these cells proved that the single individual catalytic CK2 subunit is not strictly required for cancer cell survival, these cells generally show a reduction in cell proliferation, motility/invasiveness, and an increase in sensitivity against chemotherapeutic agents when compared with wild-type cells [ 39 42 ]. Again, these effects are variably pronounced, according to the cell type and the target subunit gene.…”
Section: Non-pharmacological Ck2 Targeting Produces Antiproliferative and Pro-apoptotic Effects In Cancer Cellsmentioning
confidence: 99%
“…With the advent of the CRISPR/Cas9 tool, it has been possible to produce viable knockout cancer cells for each CK2 catalytic subunit. Even if the production of these cells proved that the single individual catalytic CK2 subunit is not strictly required for cancer cell survival, these cells generally show a reduction in cell proliferation, motility/invasiveness, and an increase in sensitivity against chemotherapeutic agents when compared with wild-type cells [ 39 42 ]. Again, these effects are variably pronounced, according to the cell type and the target subunit gene.…”
Section: Non-pharmacological Ck2 Targeting Produces Antiproliferative and Pro-apoptotic Effects In Cancer Cellsmentioning
confidence: 99%
“…Further, mutation of the three serines (99,102,103) in the HMGA1 C-terminus disrupts invasive properties of the TNBC cell line. Intriguingly, CK2 inhibitors were also found to decrease tumor cell invasion in glioblastoma cell lines (GBM) [71][72][73][74]. A recent study using organotypic GBM experimental models also found that the transcriptional repressor interferon regulatory factor 3 (IRF3) decreases invasion in GBM cells [71].…”
Section: Hmga1 Secretion and Casein Kinase 2 (Ck2)mentioning
confidence: 99%
“…For Akt phosphorylation analysis, LNCaP cells were cultured in 6-well plates for 48 h. Afterward, cells were treated with either vehicle control (1% DMSO) or 5a-2, 5b-2, or CX-4945 at 20 µM for 24 h. The cells were detached from the culture plates using cell scrapers, sedimented by centrifugation at 700 × g and 4 °C for 5 min, washed with PBS, and lysed by suspending in 100 µL homogenization buffer (50 mM Tris/HCl (pH 7.5), 1 mM EDTA, 1 mM Na 3 VO 4 , 0.5 mM NaF, 0.1 mM PMSF, 1 mM benzamidine, and 1% Triton X-100). Akt and pAkt S129 were analyzed in the cell lysates by immunoblotting as described by Schmitt et al [45] using the following antibodies:…”
Section: Analysis Of Akt Phosphorylationmentioning
confidence: 99%